FORMATION OF MONITORING AND INNOVATION SYSTEMS THROUGH DIGITAL TECHNOLOGIES IN THE MANAGEMENT OF HIGHER EDUCATION INSTITUTIONS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article provides an in-depth analysis of the role of digital technologies in the management of higher education institutions, the possibilities of forming a monitoring system through their use, and innovative approaches. The work examines the process of transition of the education system to digital management, existing problems, proposals and promising directions based on foreign experience. Solutions for controlling the quality of education and increasing the efficiency of management using digital technologies are substantiated.